Nonlinear Self-Adjointness and Nonclassical Solutions of a Population Model with Variable Coefficients - Hashemi, M. S.; İnç, Mustafa; Akgul, A.; Baleanu, D. (Amer Scientific Publishers, 2018)
In this work, the size-structured population model with variable coefficients is considered to construct the exact solutions with nonclassical symmetries in the light of the heir equations. Nonlinear self-adjointness is shown and conservation laws are calculated too. Some scientific theorems have been given in this paper.
Keywords: Population Model; Nonclassical Symmetry; Nonlinear Self-Adjointness; Heir Equations